Manipulating national identity: the strategic use of rhetoric by supporters and opponents of the 'Cronulla riots' in Australia - Bliuc, Ana-Maria; McGarty, Craig; Hartley, Lisa; Muntele Hendres, Daniela (Routledge: Taylor & Francis Group, 2012)
This research explores the role of opinion-based groups in understanding responses to racist violence such as the 2005 Cronulla riots in Australia. Traditionally, explanations of collective action in social psychology and sociology focus on conflict between broad social categories. We propose that the responses to the riots can be understood not only as inter-group conflict between Muslims and non-Muslims, or an in-group argument amongst non-Muslims, but as a bona fide inter-group conflict between supporters and opponents of the riots. We argue that these groups use rhetoric in attempts to claim dominant status within society by aligning their identities with positively valued social categories such as ethnicities and national identities. The analysis of rhetoric from the groups supporting and opposing the riots demonstrates consistent, albeit contested, attempts to align support for the riot with the Australian national category in conflict with countervailing attempts to align opposition to the riot with the same national category.